2018
DOI: 10.1212/wnl.0000000000006517
|View full text |Cite
|
Sign up to set email alerts
|

Contralesional macrostructural plasticity of the insular cortex in patients with glioma

Abstract: ObjectiveTo assess the homotopic structural plasticity in case of unilateral damage of the insula.MethodsTo detect changes in gray matter volumes of the contralesional insula from structural MRIs, we used voxel-based morphometry (VBM) in a sample of 84 patients with a diffuse low-grade glioma invading the left insula (insL group; n = 47) or the right insula (insR group; n = 37).ResultsThe region of interest–based VBM analysis highlighted a large cluster of voxels with gray matter volume increase in the contral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
80
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 28 publications
13
80
2
Order By: Relevance
“…Some studies have suggested that localized tumors can affect the function of distant part of the brain (Liu et al, 2019;Park, Kim, Kim, Kim, & Shim, 2015;Zhang et al, 2016). Indeed, structural changes in the regions distant from brain tumor have also been confirmed by some studies (Almairac et al, 2018;Bouwen et al, 2018). These structural changes have been correlated with cognition decline (Bouwen et al, 2018), though cognitive functions are not always caused by the alternation in the brain, sometimes the cognitive function recovers over time (Voytek et al, 2010), which may be attributed to the brain plasticity.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Some studies have suggested that localized tumors can affect the function of distant part of the brain (Liu et al, 2019;Park, Kim, Kim, Kim, & Shim, 2015;Zhang et al, 2016). Indeed, structural changes in the regions distant from brain tumor have also been confirmed by some studies (Almairac et al, 2018;Bouwen et al, 2018). These structural changes have been correlated with cognition decline (Bouwen et al, 2018), though cognitive functions are not always caused by the alternation in the brain, sometimes the cognitive function recovers over time (Voytek et al, 2010), which may be attributed to the brain plasticity.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, the present study was initiated to investigate the alteration in contralateral GM volume before and after surgery, and the relationship between the alterations in contralateral GM volume with cognitive function in unilateral temporal lobe glioma patients. We hypothesized that contralateral GM volume compensates for damaged glioma and the compensatory brain structure may be a structural basis of cognitive function compensation (Almairac et al, ; Bouwen et al, ; Duffau, ; Duffau, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations